PENERAPAN MODEL PEMBELAJARAN CTL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SISTEM ORGANISASI KEHIDUPAN KELAS VII-A SMP NEGERI 3 DHARMA CARAKA TELUKDALAM - Yohanna Theresia Venty Fau (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the improvement in student learning outcomes when implementing the CTL learning model at SMP Negeri 3 Dharma Caraka Telukdalam. This study is a classroom action research. The subjects of this study were students of class VII-A of SMP Negeri 3 Dharma Caraka Telukdalam. The results of the study obtained that the application of the CTL learning model in class VII-A can improve student learning outcomes where there is an increase from cycle I to cycle II. The percentage of student activity observations in cycle I is in the sufficient category. While student activity in cycle II experienced an increase, namely in the good category. Students' cognitive learning outcomes in cycle I obtained an average of 67.97 with a percentage of completion of 59.38%. In cycle II, student learning outcomes increased with an average of 80.78 with a percentage of completion of 93.75%.